KONSTRUKSI REALITAS SOSIAL DAN MAKNA DIRI PENYINTAS COVID-19 DI JAKARTA - Apriani, Vina; Utamidewi, Wahyu; Nurkinan, Nurkinan (Universitas Prof. Dr. Moestopo (Beragama), 2021)
The Covid-19 pandemic has a major impact on people's lives in Indonesia. The impact felt by the community is not only in the economic, educational, cultural sectors, but also in social interaction patterns. The aim of this research looks at the diversity of experiences and self-meanings of the Covid-19 survivor through social reality construction theory. It has an effect on change in social interactions that occur in the current era and in future lives. This study took the subject of 5 Covid-19 survivors living in Jakarta. Jakarta was chosen by researchers because that has the highest rate of Covid-19 cases in Indonesia. This study uses the theory contruction of social reality because this theory is in accordance with the research objectives.Â This theory is formed from a society that acts as a victim as well as a perpetrator in social construction and become to a social reality. This study uses the phenomenological method because it looks at the social actions taken by an individual with Covid-19. The data collection technique in this research is interviews with in-depth interviews. The results of this study are that the self-meaning of Covid-19 survivors in Jakarta is categorized into five, namely: a) Closed; b) Fear; c) Self-regret; d) Confused; e) Trauma. These five meanings are formed based on communication experiences faced by present and past survivors so that a construction of these meanings is formed.